IMPLEMENTATION OF SUGENO'S FUZZY LOGIC IN ANALYZING RICE AVAILABILITY DURING THE COVID-19 PANDEMIC AT PERUM BULOG NORTH SUMATRA - Pratiwi, Ria Widiya; Sari, Rina Filia; Widyasari, Rina (Pena Cendekia Insani, 2021)
During the Covid-19 Pandemic economic activities in North Sumatra experienced problems because many people had been laid off and lost their jobs which made them worried about reaching the staple of rice. So that the government feels the need to provide rice assistance which is directly channeled through BULOG. With this direct social assistance to the community, it could lead to instability in the rice supply and expenditure stocks until at least February 2021. So it is necessary to analyze the availability of rice at Perum BULOG so that the rice stock supply at Perum BULOG remains stable during the Covid-19 Pandemic. With fuzzy logic, Sugeno will present uncertainty, uncertainty, inaccuracy which will then produce a model of a system that is able to estimate the amount of rice supplies during the Covid-19 pandemic. In January, in the calculation of realization from North Sumatra BULOG, the ending inventory was 42,941 tonnes, while the yield from the Sugeno fuzzy method was 34,833.06 tonnes. This shows that there is a mismatch between the amount of income and expenditure of rice.